Health of children in conditions of modern society transformation - Psychological aspect - Nikitenko, Anastasia; Antsiferova, Natalya; Seluch, Marina; Ismailova, Zukhra (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the work is to compare the questionnaire indicators of children of 11 years old from groups of different origin and social status. The assessment of basic family values in groups of children was performed, also the comparison of positive and negative qualities in the family, according to children; identification of differences in family values and qualities between different groups of children. The studies were conducted in 2019 among 1000 children and their parents in Moscow (Russia). Children were divided into 4 groups of 250 people. Group 1 included children from wealthy families studying at the lyceum, group 2 - the same, but from secondary schools, Group 3 - children from low-income and incomplete families, Group 4 - children of migrants (1st generation). Children were questioned in order to identify the main positive and negative characteristics of families. Parents’ survey was conducted in order to identify methods of exposure. Anonymity was preserved.The level of material wealth and social status was established to have a positive relationship with the number of social network accounts (Pearson correlation 0.95), and with the presence of social networks of foreign origin in them (Pearson correlation 0.90 for groups 1 and 2 and -0.99 for groups 3 and 4). Differences were established for the indices of cooperation and care, the distribution of roles in the family, as well as for the presence of clear rules in the family. In group 3, these indicators are minimal in relation to groups 1 and 2 (p≤0.001), group 4 (migrants) occupies an intermediate position between group 3 and first two groups.Social networks massively form infantile, socially maladaptive children who are not adapted to the realities of life due to the lack of active creative search. A similar negative effect has pastime on the street. The financial and social status of the family does not determine the level of mental health of children.